Effectiveness of Nurse-Driven Discharge Teaching Using Mobile Application for Home-Based Health Care Practices among Postoperative Neurosurgical Patients or Caregivers in a Tertiary Care Hospital, New Delhi: A Randomized Control Study - Metilda, C.J.; Sharma, Kamlesh K.; Sinha, Aditi P.; Agrawal, Deepak (Indian Journal of Neurotrauma, 2021)
Introduction Considering the increased access to mobile use even in the remote areas, it may be feasible to utilize mobile application (App)-based education among neurosurgical patients and caregivers for home-based care.Objective This study was aimed to assess the effectiveness of nurse-driven discharge teaching using mobile App for home-based health care practices in terms of discharge advice compliances, revisits, and satisfaction among postoperative neurosurgical patients.Materials and Methods This randomized control trial was conducted among 100 (50 in each arm) postoperative neurosurgical patients admitted to Neurosurgery department, All India Institute of Medical Sciences (AIIMS), New Delhi. The experimental group received mobile App–based discharge teaching additional to the routine paper-based discharge teaching received by the control group. Data were collected at baseline, during first (within 30th day) and second (within 60th day) routine follow-up visits using adherence to refills and medications scale (ARMS) questionnaire (medication compliance), self-developed structured questionnaires (lifestyle practices like tracheostomy tube (TT) catheter care, exercises and diet changes, revisits, and satisfaction) and computerized log record from App. Data were analyzed using descriptive and inferential statistics.Results The demographic and clinical profiles of both groups were comparable. There was no statistically significant difference in medication compliance between the experimental group and control group (p = 0.35 and 0.53) in first and second posttests, respectively. The level of confidence to perform lifestyle practices was high among experimental group. The subgroup analysis showed that patients in experimental arm were more compliant to medications as compared with control group (p = 0.001). Both the groups were comparable in terms of revisits (p = 0.26). However, the overall satisfaction of experimental group was reported to be highly using mobile App based teaching than control group with routine paper-based discharge teaching (p = 0.001).Conclusion Nurse-driven discharge teaching using mobile App is an effective method for neurosurgical patients to adhere to home-based discharge teachings. Use of technology like mobile Apps in vernacular language can bridge the gap for improving home-based care and follow-up among patients in resource constrained settings.
Keywords: lifestyle practices; medication compliance; mobile app–based discharge; nurse-driven discharge teaching; postoperative neurosurgery patient